Measuring cerebral glucose metabolism by chemical exchange-sensitive spin-lock (CESL) MRI of 2-deoxy-D-glucose in rodents - Philipp Boehm-Sturm; Patrick Schuenke; Marco Foddis; Susanne Mueller; Stefan P. Koch; Daniel J. Beard; Paul Holloway; Amin Mottahedin; Leif Schröder; Alastair M. Buchan; Philipp Mergenthaler (PLoS ONE, 2026)
Magnetic resonance imaging (MRI) of glucose metabolism shows significant potential for identifying disease biomarkers and monitoring therapeutic responses in neurological conditions. Here, we present a protocol utilizing chemical exchange-sensitive spin-lock (CESL) MRI with the glucose analogue 2-deoxy-D-glucose (2DG) in the rat brain. We employed this method to characterize metabolic changes in ischemic tissue in a rat model of stroke. However, the utility of the technique is not limited to stroke and may be adapted to other disease models with minimal modifications. Previous research has demonstrated that CESL MRI is sensitive to various glucose analogs, including regular D-glucose, which is suitable for human application. Consequently, our protocol provides a foundation for a wide range of future applications in both basic and translational research, with potential utility in animal models and, eventually, human studies.